Effectiveness and feasibility of structured emotionally focused family therapy for parents and adolescents: Protocol of a within-subjects pilot study - Conradi, Henk Jan; Meuwese, Daphne; Rodenburg, Lenny; Dingemanse, Pieter; Mooren, Trudy (PloS one, 2023)
Mental health issues are widespread among children and adolescents worldwide. Although mental health difficulties may manifest themselves in many different diagnoses, there is growing support for a limited number of underlying transdiagnostic processes. Attachment encompasses a key transdiagnostic mechanism, namely emotional regulation. This study protocol aims to evaluate the feasibility and potential effectiveness of structured emotionally focused family therapy (EFFT), the goal of which is to develop secure attachment between parents and their children to reduce children’s vulnerability to mental health problems. A within-subjects design with three waves, a waiting period, treatment, and follow-up, will be conducted. Families will serve as their own controls. Approximately 15 to 20 families with adolescents (aged 12−18 years) as the ‘identified patients’ will be included. They will participate in 16−21 sessions of EFFT. The study will use a multi-method approach. Self-report questionnaires will be administered repeatedly (i.e., pre-waiting period, pre-treatment, halfway treatment, post-treatment, and follow-up), measuring parent-adolescent attachment, partner-partner attachment, negative interactions, and adolescent psychological complaints. Multi-level analyses will be conducted. Semi-structured interviews will be administered at follow-up to evaluate feasibility and acceptability of EFFT. Treatment integrity will be assessed. The present study is the first to evaluate feasibility of structured EFFT and obtain a first impression of its effectiveness. This information will help us to improve EFFT. Limitations are discussed. Trial registration: Recruitment commenced in June 2022. The approximate trial duration is 36 months. The trial was registered at ClinicalTrials.gov ( NCT05657067 ) on December 9, 2022, and Open Science Framework ( https://osf.io/39dt2/ ) on June 14, 2022.